Injecting rabies immunoglobulin (RIG) into wounds only: A significant saving of lives and costly RIG - Omesh Kumar Bharti; Shampur Narayan Madhusudana; Henry Wilde (Taylor & Francis Group, 2017)
An increasing number of dog bite victims were being presented to public hospitals in Himachal Pradesh in 2014 amidst virtual non availability of any rabies immunoglobulin (RIG). Only a small quantity of equine rabies immunoglobulin (eRIG) was available from the government owned Central Research Institute (CRI) Kasauli. This available eRIG was used in 269 patients as an emergency response and only for local infiltration of severe bite wounds by suspected rabid dogs. This was followed by rabies vaccination, using the WHO approved intra-dermal Thai Red Cross Society vaccination schedule. A subgroup of 26 patients were later identified who had been severely bitten by laboratory confirmed rabid dogs. They were followed for more than one year and all were found to be alive.